Incorporating Real Time Ultrasound Guidance to Kidney Biopsy by the Nephrologist: An Educational Video - Hassanzadeh Rad , Afagh; Badeli, Hamidreza (Journal of Pediatric Nephrology, 2020)
Kidney biopsy is an important technique for diagnosis and management of patients with kidney diseases. Real-time US with guided renal biopsy is a consolidated method. This method obtained over 90% of adequate samples. Even reduction of complications has been obtained from blind technique (10%) to an ultrasound-guided method (2-6%). in this article authors aimed to show a video to visualize a sample of kidney biopsy under guidance of US on a 14-year-old girl.